Estimating Flood Catastrophe Bond Prices Using Approximation Method Of The Loss Aggregate Distribution: Evidence From Indonesia - Riza Andrian Ibrahim; Sukono; Herlina Napitupulu; Rose Irnawaty Ibrahim; Muhamad Deni Johansyah; Jumadil Saputra (Growing Science, 2024)
Indexed by WOS/Scopus